Is MicroRNA-127 a Novel Biomarker for Acute Pancreatitis with Lung Injury?. (24th December 2017) - Shi, Na; Deng, Lihui; Chen, Weiwei; Zhang, Xiaoxin; Luo, Ruijie; Jin, Tao; Ma, Yun; Du, Chen; Lin, Ziqi; Jiang, Kun; Guo, Jia; Yang, Xiaonan; et al.
Abstract : Background and Aims . The aim of this study was to determine the expression of microRNA-127 (miR-127) in both rat models and patients of acute pancreatitis (AP) with lung injury (LI). Methods . Rats were administrated with retrograde cholangiopancreatography injection of 0.5% or 3.5% sodium taurocholate to induce AP with mild or severe LI and were sacrificed at 6, 12, and 24 h. Rats from the control group received a laparotomy only. Plasma from a prospective cohort of AP patients was collected. The levels of miR-127 in the tissues and plasma were detected using quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Results . The upregulation of miR-127 in the lungs of rats was detected in the groups of AP with severe LI at 6 h and 24 h, whereas it was scarcely detectable in plasma. In the pilot study that included 18 AP patients and 5 healthy volunteers, the plasma miR-127 level was significantly downregulated in AP patients with respiratory failure compared with the healthy volunteers (P = 0.014 ) and those without respiratory failure (P = 0.043 ). Conclusion . miR-127 might serve as a potential marker for the identification of AP with LI.